Risk Communication and Public Health Emergency Responses During COVID-19 Pandemic in Rural Communities in Kenya: A Cross-Sectional Study - Wilberforce Cholo; Fletcher Njororai; Walter Ogutu Amulla; Caleb Kogutu Nyaranga (COVID)
Background: The COVID-19 pandemic highlighted the crucial role of community preventive behaviors in controlling the virus’ spread. Studies show that people’s risk perceptions and awareness significantly contribute to the containment and prevention of infections by motivating adoption of desired actions and behaviors. This study aimed at assessing the role of risk communication and factors that influenced responses during the COVID-19 pandemic in rural communities in Western Kenya. Methods: A descriptive cross-sectional study was conducted using a quantitative research approach, collecting data from 806 individuals across Kisumu, Vihiga, and Kakamega counties. Descriptive statistics were used to detail the demographic characteristics of the study population, while logistic regression analysis estimated the associations between risk communication and demographic characteristics on COVID-19 vaccine acceptance, compliance with mitigation behaviors, perceived severity, and perceived susceptibility. Results: The results showed that 55% of participants were male and 45% were female, with an average moderate compliance with safety measures (mean = 5.15). A significant portion of participants wore face masks (85.3%), practiced hand hygiene (78.9%), and avoided close contact behaviors (66.6%). Most respondents received information through mass media (86.1%) and health workers (72.9%). Compliance with COVID-19 mitigation measures was highest among those who trusted information from official institutions, health professionals, and mass media, compared to social media, with increased odds of 2.7 times and 2.5 times, respectively. Higher risk perception was significantly associated with older age groups (above 50 years), being male, and working in the private sector. Effective risk communication significantly influenced risk perception, compliance with COVID-19 measures, and vaccination acceptance. Conclusions: The findings suggest that effective risk communication strategies are critical during public health emergencies and hence implications for future public health crises. The results underscore the importance of targeted communication and tailored interventions to improve compliance and vaccine acceptance among different demographic groups, ensuring a more robust public health response during outbreaks and pandemics.